Determinants of survival after lung transplantation in telomerase‐related gene mutation carriers: A retrospective cohort. Issue 4 (28th December 2021) - Phillips‐Houlbracq, Mathilde; Mal, Hervé; Cottin, Vincent; Gauvain, Clément; Beier, Fabian; Sicre de Fontbrune, Flore; Sidali, Sabrina; Mornex, Jean François; Hirschi, Sandrine; Roux, Antoine; Weisenburger, Gaelle; Roussel, Arnaud; et al.
Abstract : Carriers of germline telomerase‐related gene (TRG) mutations can show poor prognosis, with an increase in common hematological complications after lung transplantation (LT) for pulmonary fibrosis. The aim of this study was to describe the outcomes after LT in recipients carrying a germline TRG mutation and to identify the predictors of survival. In a multicenter cohort of LT patients, we retrospectively reviewed those carrying pathogenic TRG variations ( n  = 38; TERT, n  = 23, TERC, n  = 9, RTEL1, n  = 6) between 2009 and 2018. The median age at LT was 54 years (interquartile range [IQR] 46–59); 68% were male and 71% had idiopathic pulmonary fibrosis. During the diagnosis of pulmonary fibrosis, 28 (74%) had a hematological disease, including eight with myelodysplasia. After a median follow‐up of 26 months (IQR 15–46), 38 patients received LT. The overall post‐LT median survival was 3.75 years (IQR 1.8‐NA). The risk of death after LT was increased for patients with myelodysplasia (HR 4.1 [95% CI 1.5–11.5]) or short telomere (HR 2.2 [1.0–5.0]) before LT. After LT, all patients had anemia, 66% had thrombocytopenia, and 39% had neutropenia. Chronic lung allograft dysfunction frequency was 29% at 4 years. The present findings support the use of LT in TRG mutation carriers without myelodysplasia. Hematological evaluation should be systematically performed before LT. Abstract : Among patients with telomerase‐related gene mutations who undergo lung transplantation for idiopathic pulmonary fibrosis, pre‐transplant myelodysolasia is associated with reduced post‐transplant survival.